Locked intramedullary nailing provides superior functional outcomes and lower complication rates than plate fixation of distal fibula fractures. A systematic review and meta-analysis of comparative studies. Issue 7 (October 2022) - Attia, Ahmed Khalil; Fayed, Aly; Mahmoud, Karim; Labib, Sameh A.; Aydogan, Umur; Juliano, Paul
Graphical Abstract: ga1 Abstract: Purpose: This study aims to provide an updated systematic review and meta-analysis of comparative studies on the outcomes and complications of locked IMNs in comparison to ORIF using plates and screws, while avoiding limitations of similar published reviews. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, two independent team members electronically searched MEDLINE (PubMed), EMBASE, Google Scholar, SCOPUS, and Cochrane databases throughout May 2021 using the following keywords with their synonyms: "Ankle fracture fixation" AND "Open reduction and internal fixation", "locked intramedullary nail", or "complications". The primary outcomes were (1) functional outcomes, (2) complications, and (3) reoperation, while the secondary outcomes were: (1) union rate, and (2) cost. Inclusion criteria: comparative studies on outcomes and complications of plate open reduction and internal fixation (ORIF) vs. locked intramedullary nailing (IMN) of ankle fractures reporting at least one of the following parameters: functional outcomes, complications (infection, dehiscence, reoperation etc.), union, and cost. Studies reporting on non-locked intramedullary fibular nails were also excluded. Results: After the removal of duplicates, a total of 1461 studies were identified. After screening those records, 63 studies remained for full-text assessment. Out of those, four comparative studies with a total of 262 ankle fractures met the inclusion criteria for this meta-analysis. The mean 12 months postoperative Olerud and Molander Ankle Scores (OMAS) were reported by two studies, with a statistically significant difference in favor of IMNs (MD= 6.72, CI: 3.77–9.67, p <0.001, I 2 = 94%). I n the ORIF group, the overall complication rate was 39/134 (29.1%) vs. 10/128 (7.8%) in the IMN group, with a statistically significant difference in favor of the IMN group (RR=3.23, CI:1.71–6.11, p <0.001, I 2 =34%). In the ORIF group, the overall infection rate was 11/134 (8.2%), while there were no infections in the IMN group, with a statistically significant difference in favor of the IMN group (RR=8.05, CI:1.51–42.82, p =0.01, I 2 =0%). In the ORIF group, the overall reoperation rate was 10/134 (7.5%) while the overall reoperation rate was 6/128 (4.7%) in the IMN group, with no statistically significant difference between groups (RR=1.49, CI: 0.60–3.70, p  = 0.39, I 2 =0%). Conclusion: Locked intramedullary nail fixation of distal fibula fractures could provide superior functional outcomes and lower complication rates in comparison to open reduction and plate fixation. Despite the high incidence of ankle fractures, the number of high-quality comparative studies remains limited in literature, especially on newer locked fibular nails, and large multicentric clinical trials are required before recommending locked IMNs as the new standard of care in distal fibula fractures.